Sosialiasi Membangun Jiwa Bisnis yang Tangguh bagi Jemaat GKP Kramat - Jakarta Pusat - Carolina F. Sembiring; Juaniva Sidharta; Lenny Panggabean; Nenny Anggraini; Arya Gina Tarigan; Rutman Lumbantoruan; Fine Tiara (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Entrepreneurship is the process of creating, developing, and managing a business with the goal of generating profit through products, services, or innovations that meet market needs. The role of entrepreneurship is highly significant, as it greatly contributes to economic growth, social development, and the improvement of societal welfare in a country. The KPEJ GKP Kramat program in Central Jakarta views the enhancement of entrepreneurial spirit among its congregation as an important initiative, particularly in encouraging women to create home-based business opportunities as an alternative means to strengthen their family’s economy. This initiative arises from the fact that interest and participation in entrepreneurship among the congregation remain relatively low. Therefore, the challenge lies in how to foster entrepreneurial spirit and mindset—building the right way of thinking, recognizing and starting a business by understanding opportunities and risks, preparing financial plans, and developing business proposals or business model canvases. This community service activity aims to provide socialization on the importance of developing entrepreneurial spirit and mentality by utilizing available business opportunities for the congregation of GKP Kramat, Central Jakarta. The program is conducted onsite and is expected to have a positive impact by increasing interest and encouraging members to start their own businesses, thereby helping improve their family’s economic well-being.